Resilience System National In The Perspective Of Utilitarianism - Dedy Ismanto; Bayu Bayu (International Asia Of Law and Money Laundering (IAML), 2022)
The importance of optimal health services can be seen from the consideration and general explanation of Law No. 36 of 2009 on health, in the event of health problems, it will lead to a decrease productivity and if productivity falls, then National Development will be hampered, meaning here it can be concluded, that health must be a concern for all elements, because all elements have the same interests and goals that lead to a smooth National Development, so that welfare can be realized that can be achieved with productivity obtained by striving for health services in order to, The question that arises is whether the implementation of the National Health System as formulated in the legislation can bring as many benefits as possible people? .The principle of expediency is strongly influenced by the thought of utilitarianism, namely that the law was created to realize happiness for as many people as possible so that the benefits of the law can be felt by as many people as possible, in terms of harmonization of Law No. 36 of 2009 on health and all elements related to Law No. 36 in 2009 on health , the maximum benefit for all elements of society can be realized if social justice can be realized, thus: if the welfare gap can be reduced, then social justice can be realized; it can happen if there is maximum economic productivity, then every citizen can feel the benefits of management of production branches that are important and concern the lives of many people.